Sustainable Tourism: The Future of 2050 in Terms of Innovation, Technology, and Resilience of Tourism Destinations - Furqan Furqan; Yogi Putra; Femmy Indriany Dalimunthe (Lembaga Pengembangan Kinerja Dosen, 2026)
The tourist industry is undergoing a significant upheaval, owing to technology improvements, sustainability demands, and rising global uncertainties such as pandemics, climate change, and economic crises. The purpose of this study is to look at the future of sustainable tourism in 2050 by studying the interaction between innovation, digital technology, and tourist destination resilience. The study performed a Systematic Literature Review (SLR) in conjunction with bibliometric analysis. Data were gathered from scholarly papers indexed in Google Scholar, Scopus, and Web of Science databases, then chosen using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. According to the findings, contemporary tourism studies have emphasized innovation, smart tourism technology, and destination resiliency. Artificial Intelligence (AI), Big Data, Internet of Things (IoT), Augmented Reality (AR), and digital platforms all play important roles in improving destination management, boosting guest experiences, and achieving sustainability objectives. Furthermore, destination resilience is acknowledged as an important aspect in dealing with future crises and guaranteeing long-term tourist viability. The report presents an integrated framework and roadmap for 2050 that focuses on the synergy of innovation, technology, and resilience as the foundation for future intelligent, adaptable, and sustainable tourist destinations.